Screening for Human Immunodeficiency Virus in Inner City Females With Abnormal Cervical Cytology - T. Scott Jennings; Peter Dottino; Rhoda Sperling; Ann Marie Beddoe (Hindawi Limited, 1996)
Objective: This report evaluates the acceptance, results, and predictors of human immunodeficiency virus (HIV) infection in inner city women referred to a colposcopy clinic for abnormal cervical cytology.